Integration of Islamic Religious Education Based on Gender-Responsive Pedagogy in Shaping the Moderate Character of Madrasah Students in the Digital Era - Mohammad Rifki; Mukhlisin Mukhlisin; Muhammad Anis Fuadi (Yayasan Zia Salsabila, 2026)
This study aims to analyze the integration of Islamic Religious Education based on gender responsive pedagogy in shaping moderate character among madrasah students in the digital era. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of Islamic Religious Education teachers, madrasah principals, and students selected through purposive sampling. Data were collected through observation, interviews, and documentation, while data analysis used the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings revealed that the integration of gender responsive pedagogy in Islamic Religious Education created an inclusive, participatory, and democratic learning process. Teachers provided equal opportunities for male and female students in classroom activities, discussions, and group leadership. This implementation positively contributed to the development of students’ moderate character, including tolerance, respect for differences, anti-discrimination attitudes, and polite interaction in digital spaces. Furthermore, the use of digital media in learning helped students understand the importance of religious moderation and digital literacy in everyday life. This study concludes that the integration of Islamic Religious Education based on gender responsive pedagogy can become an effective strategy for shaping moderate student character in the digital era.